KETERAMPILAN MENULIS KARYA ILMIAH UNGGULAN KEPALA SEKOLAH DAN GURU SEKOLAH DASAR DI LINGKUNGAN KECAMATAN CIBINONG - Supriatnoko, Supriatnoko; Redyanita, Hastuti (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2020)
The community service activities carried out are training activities in writing superior scientific works. This training is important because the demands of expertise and attention to the value of great benefits as the competence of a principal and elementary school teachers in addition to the ability and skills in teaching subjects so that the professionalism of a principals and teacher is also reflected in his ability to write superior scientific works. This training was held for 2 days (7-8 October 2019) in the Hall of the KLP Office Cibinong Sub-District, Bogor Regency, with 40 participants, the determination was determined based on the purposive sampling method, representing 10 Teacher Working Group Clusters in the Cibinong Sub-District Environment. This training is indoor, meaning the activities are carried out in the hall. The delivery techniques uses lecture, question and answer, discussion, independent work, and structured assistance. Participants are guided and assisted to be able to produce a scientific work, in the form of papers or in the form of scientifric articles. From the results of this training activity 100% of the participants can produce a scientific work that he wrote independently.